2012
DOI: 10.1371/journal.pone.0049563
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Suppressors of the Sin3A Knockdown Wing Phenotype

Abstract: The role of the Sin3A transcriptional corepressor in regulating the cell cycle is established in various metazoans. Little is known, however, about the signaling pathways that trigger or are triggered by Sin3A function. To discover genes that work in similar or opposing pathways to Sin3A during development, we have performed an unbiased screen of deficiencies of the Drosophila third chromosome. Additionally, we have performed a targeted loss of function screen to identify cell cycle genes that genetically inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 119 publications
(150 reference statements)
1
9
0
Order By: Relevance
“…In addition, the earlier effort demonstrated that Sin3A activity is regulated through the Wnt/β-catenin signaling pathway in Drosophila development27. On this basis, we tested whether Wnt/β-catenin and Shh signaling pathways were involved in neuronal differentiation induced by Sin3A knockdown in pluripotent P19 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the earlier effort demonstrated that Sin3A activity is regulated through the Wnt/β-catenin signaling pathway in Drosophila development27. On this basis, we tested whether Wnt/β-catenin and Shh signaling pathways were involved in neuronal differentiation induced by Sin3A knockdown in pluripotent P19 cells.…”
Section: Resultsmentioning
confidence: 99%
“…RNAi screens performed in cultured cells revealed that SIN3 is a putative regulator of neural and cardiac development as well as an active player in ERK and JNK signaling [19, 20]. A recent genetic screen to identify suppressors of the Sin3A knockdown curved wing phenotype found that genes involved in multiple processes during development, including regulation of the cell cycle, Wnt signaling, metabolism and transcription, interacted with Sin3A [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Because SIN3 is part of an HDAC complex, which contains both a histone deacetylase RPD3 and a histone demethylase dKDM5/LID (15,16), we asked whether the increase of both H3K9ac and H3K4me3 at the promoters of methionine metabolism genes in Sin3A knockdown cells is due to instability of the complex and degradation of RPD3 and dKDM5/LID following knockdown of Sin3A. Our published RNA-Seq data indicate that the expression of rpd3 and lid is not changed when SIN3 is decreased (16).…”
Section: Sin3 Regulates Expression Of Methionine Metabolic Genes and mentioning
confidence: 99%
“…In Drosophila and mammals, a histone demethylase is also part of a SIN3/RPD3 HDAC complex (14). We previously reported a genetic interaction between Drosophila Sin3A and the genes encoding the histone demethylases KDM2 and dKDM5/LID (15,16). These biochemical and genetic data suggest that the SIN3 complex may regulate histone methylation in addition to histone acetylation.…”
mentioning
confidence: 89%
See 1 more Smart Citation